«Hard» and «Soft» Ukrainian Dialect Variants (Linguostylistic Studies, 2018)
It is a fact of common knowledge, that Western Polissia consists of three parts, and they are the parts of different states: Volynian Polissia (Ukraine), Beresteyshchyna (Republic of Belarus) and Podlasie (Republic of Poland). Eastern Slavic dialects are commonplace along the eastern border of the Republic of Poland on Podlasie, which are territorially divided into the Southern-Eastern (Lublin Voivodship) and the North Podlasky dialects (Podlaskie, formerly the Belostok Voivodship). Many old-established features can be traced in the Ukrainian dialects that are spoken beyond the bounds of modern Ukraine since there is almost no contact with other main dialects in this area. Even the dwellers of these territories feel sometimes vexed regarding the key question: what language is their language - Ukrainian, Belarusian, Russian or Polish? Indigenous inhabitants of these territories comprehend the dialectal peculiarities of their speech, but they can not always determine which language their dialect belongs to. However, all respondents determine one thing unmistakably: their dialects do not belong to the Belarusian language. To define their speech they use the names: simple language, Orthodox, Russian, Hahlats'ka, tuteisha, but specify that their language is closest to the Ukrainian language. Note that the local term Hakhlats’ka language is used in a neutral sense. Since the dialect speakers can not define their dialect, they can not correctly determine their national affiliation: they call themselves Orthodox, Rus’ki, Hakhly, tuteishni, etc.In addition, the dialect speakers themselves divide this language into soft and hard, according to the pronunciation of the sound combinations: [ли/ly] (khodyly) – [лʹі] (khodily, khodilі), [не/ne] (nedaleko) – [нʹе] (niedalieko), [ди/dy] (odyn) – [дʹі] (odin), [си/sy] (syrota) – [сʹі] (sirota), etc.
Keywords: Podlaskie; Podlaskie dialects; Ukrainian (Hakhlats'ka) language; hard and soft pronunciation of front-lingual consonants